Optical characterization of type-I to type-II band alignment transition in GaAs/AlxGa1−xAs quantum rings grown by droplet epitaxy. (20th July 2017) - Su, Linlin; Wang, Ying; Guo, Qinglin; Li, Xiaowei; Wang, Shufang; Fu, Guangsheng; Mazur, Yuriy I; Ware, Morgan E; Salamo, Gregory J; Liang, Baolai; Huffaker, Diana L
Abstract: Optical properties of GaAs/Al x Ga1− x As quantum rings (QRs) grown on GaAs (1 0 0) by droplet epitaxy have been investigated as a function of the Al-composition in the Al x Ga1− x As barrier. A transition from type-I to type-II band alignment is observed for the QRs via photoluminescence (PL) and time-resolved photoluminescence (TRPL) measurements. While x ⩽ 0.45, the QR PL spectra show a blue-shift and an increasing intensity with increasing Al-composition, revealing the enhancement of quantum confinement in the QRs with type-I band alignment. While x ⩾ 0.60, the characteristic large blue-shift with excitation intensity and the much longer lifetime indicate the realization of a type-II band alignment. Due to the height fluctuation of QR structures grown by droplet epitaxy mode, it is not the large blue-shift of emission energy, but the long lifetime that becomes the more important feature to identify the type-II band alignment.